(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Since the time of the Prophet, may God’s prayers and peace be upon him, and the Rightly Guided Caliphs, the Arab Islamic community witnessed a mixing between the most of elements that joined under the banner of Islam and became defenders of it and those working to spread it. Indeed, some foreigners preceded the Arabs themselves in entering Islam, and they gained the appreciation of the Arabs, and rose The foreigners, in turn, were able to form special ties in social life, so they came into contact with the Arabs through intermarriage, and worked in administrative jobs and provided various services, but this would not find its place among the Umayyads who were intolerant of the Arab element, and worked to get rid of them little by little, because they saw growing threat to their authority and lineage, and despite the adherence of the Rightly Guided Caliphs and those who supported them among the Arabs to the principle of equality between Arabs and non-Arabs, some of the nobles and tribal chiefs abhor this, and incite the Caliphs that they prefer the nobles of the Arabs and the Quraysh over the foreigners, so it is difficult to be certain. The mawali and non-Arabs in the time of the Prophet and the Rightly Guided Caliphs were enjoying equality, and they walked side by side with the Arabs, in addition to the fact that the first Muslims from the Persians were an aid to the Arabs in establishing authority. We enliven them and introduce them to those who remained in custody, and they were a means of communication between the two parties in various fields.